INFLUENCE OF ANTHROPOMETRIC CHARACTERISTIC IN MANIFESTATION EXPLOSIV FORCE OF FOOTBALLERS AGE - Ibri Lulzim; Prizreni Sahit; Shala Sylejman; Shala Shkelzen (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
With a purpose to investigate the influence of anthropometric characteristic in manifestation explosive force were organized one experimental study with one Sample from 120 footballer age 16 ± for six months, For purposes of this study were used anthropometric characteristic battery from 8 tests which were component in predict variables, and for estimation of explosive force were implicated two tests which were component in variables criterion system. Information were realized by using regressive and descriptive analysis. Based in investigation results can be concluded, that implicated system of anthropometric characteristic has important influence in manifestation of explosive force to footballer age 16 means that prediction tests of explosive force according to measure of anthropometric characteristic is possible.